Blow-up of Solution for Initial Boundary Value Problem of Reaction Diffusion Equations - Baomin, Qiao (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In this paper, the blow-up of solution for the initial boundary value problem of a class of reaction diffusion equations with multiple nonlinearities is studied. We prove, under suitable conditions on memory and nonlinearities term and for negative or positive initial energy, a global nonexistence theorem.